The Harvard Business Review Entrepreneur's Handbook - Review, Harvard (Ascent Audio, 2019)
The one primer you need to develop your entrepreneurial skills. Whether you're imagining your new business to be the next big thing in Silicon Valley, a pivotal B2B provider, or an anchor in your local community, the Harvard Business Review Entrepreneur's Handbook is your essential resource for getting your company off the ground. Starting an independent new business is rife with both opportunity and risk. And as an entrepreneur, you're the one in charge: your actions can make or break your business. You need to know the tried-and-true fundamentals-from writing a business plan to getting your first loan. You also need to know the latest thinking on how to create an irresistible pitch deck, mitigate risk through experimentation, and develop unique opportunities through business model innovation. The Harvard Business Review Entrepreneur's Handbook addresses these challenges and more with practical advice and wisdom from Harvard Business Review's archive. Keep this comprehensive guide with you throughout your startup's life-and increase your business's odds for success.